Form of Power Pressure in The Short Stories Shooting an Elephant by George Orwell and Pelajaran Pertama Bagi Calon Politisi by Kuntowijoyo - Azahra Fadiliawati Agustin; Ujang Suyatman; Lili Awaludin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the forms of power pressure and their influence on the decision-making process of the main characters in the short stories Shooting an Elephant by George Orwell and Pelajaran Pertama Bagi Calon Politisi by Kuntowijoyo. This study uses a descriptive qualitative approach with a power discourse analysis method based on Michel Foucault's theory. Data sources include narrative excerpts, dialogues, and actions of characters that represent power pressure in both short stories. Data collection techniques were carried out through intensive reading (close reading), while data analysis was carried out through the stages of classifying the forms of power pressure (social, ideological, psychological, and symbolic) and interpreting their influence on the characters' decisions. The results show that power pressure in both short stories is not always present in the form of physical coercion, but operates subtly through discourse, social norms, mass expectations, and normalized political practices. In the short story Shooting an Elephant, mass pressure and the demand to maintain a colonial image force the characters to make decisions that contradict their conscience. Meanwhile, in the short storyPelajaran Pertama Bagi Calon Politisi, ideological pressure and political pragmatism push the characters to sacrifice moral idealism for the sake of power. Thus, this study confirms that power works productively through the internalization of norms that shape ways of thinking and limit the choices that are considered possible, so that the character's decisions are the result of discursive pressure, not entirely free will.